Antral membrane balloon technique versus Densah bur in crestal sinus lift with simultaneous implant placement: a randomized clinical trial - Mohamed Mahmoud Alajami; Heba Abo-Elfetouh Elsheikh; Shaimaa Ahmed Abo El-Farag; Noha Ahmed Mansour (BMC, 2024)
Abstract Background The posterior maxilla presents challenges for implant insertion because of the poor bone quality as well as the loss of vertical bone height. Indirect transcrestal sinus lift techniques are advised when a few millimeters of additional height are needed. This study aimed to evaluate the clinical and radiographic outcomes of antral membrane balloon technique versus Densah burs for transcrestal maxillary sinus lifting with simultaneous implant placement. Materials and methods This randomized clinical trial was conducted on 22 patients received 32 dental implants for replacement of missed maxillary posterior teeth after crestal maxillary sinus lifting. The patients were randomly divided into two groups. Group 1, patients underwent crestal sinus floor elevation with simultaneous implant placement using antral membrane balloon technique. Group 2, patients underwent crestal sinus floor elevation with simultaneous implant placement using Densah burs. Patients were evaluated clinically and radiographically using cone beam computed tomography (CBCT) at regular time intervals immediately, 6 months and 12 months after surgery. All clinical and radiographic parameters were statistically analyzed. Results All dental implants were successful for 12 months of follow up. Regarding implant primary stability, there was a statistical significant difference between the study groups in favor of Densah group (P = 0.004), while there was no significant difference after 6 months (P = 0.07). Radiographically, balloon group showed a statistically significant immediate postoperative vertical bone height (P < 0.0001), and significant reduction in vertical bone height after 6 months (P < 0.0001). Densah group showed significant increase in bone density (P ≤ 0.05). Conclusion Both techniques demonstrated successful clinical and radiographic outcomes for crestal sinus lift. The antral membrane balloon group demonstrated better immediate postoperative vertical bone gain, while Densah burs had higher implant primary stability and bone density. Trial registration This study was registered in Clinical-Trials.gov PRS ( https://register.clinicaltrials.gov ) under identification number NCT05922592 on 28/06/2023.